Bangladesh : Financial Sector Distress and Lost Economic Growth - Kojo, Naoko (World Bank, Washington, DC, 2013)
The financial system in Bangladesh has suffered from years of systemic and chronic problems, represented by weak supervision and enforcement, deficient accounting and reporting practices, and more importantly, widespread loan defaults and delinquencies. It is widely perceived that major inadequacies in the financial sector have had a considerable growth restraining effect over the years, by inhibiting private investment activities and productivity growth, as well as promoting misallocation of resources. It is paramount important that the government takes an urgent policy action to reform the mal-functioning financial sector. The main objective of such reforms is to develop a market oriented, disciplined modem system for mobilization of resources, efficient allocation of resources from both domestic and foreign sources, and reduction of poverty through sustained economic growth. This paper is organized as follows. Section two reviews the recent theoretical and empirical literature on finance and growth. Section three summarizes the main findings of our cross-country analysis, conducted to estimate the growth impact of financial sector distress in Bangladesh. Finally, section four concludes the paper.